Stratified glucose-lowering response to vildagliptin and pioglitazone by obesity and hypertriglyceridemia in a randomized crossover trial - Brandon, Rebecca; Jiang, Yannan; Yeu, Rui Qian; Tweedie-Cullen, Ry; Smallman, Kate; Doherty, Glenn; Macaskill-Smith, Kerry A.; Doran, Rebekah J.; Clark, Penny; Moffitt, Allan; Merry, Troy; Nehren, Norma; et al. (Frontiers in Endocrinology, 2023)
Background: Understanding which group of patients with type 2 diabetes will have the most glucose-lowering response to certain medications (which target different aspects of glucose metabolism) is the first step in precision medicine. Aims: We hypothesized that people with type 2 diabetes who generally have high insulin resistance, such as people of Māori/Pacific ethnicity, with obesity and/or hypertriglyceridemia (OHTG), would have greater glucose-lowering by pioglitazone (an insulin sensitizer) versus vildagliptin (an insulin secretagogue). Methods: A randomised, open-label, two-period crossover trial was conducted in New Zealand. Adults with type 2 diabetes, HbA1c>58mmol/mol (>7.5%), received 16 weeks of either pioglitazone (30mg) or vildagliptin (50mg) daily, then switched over for another 16 weeks of treatment. Differences in HbA1c were tested for interaction with ethnicity or OHTG, controlling for baseline HbA1c using linear mixed models. Secondary outcomes included weight, blood pressure, side effects, and diabetes treatment satisfaction. Results: 346 participants were randomised (55% Māori/Pacific) between February 2019 to March 2020. HbA1c after pioglitazone was lower than after vildagliptin (mean difference -4.9mmol/mol [0.5%]; 95% CI -6.3, -3.5; p<0.0001). Primary intention-to-treat analysis showed no significant interaction effect by Māori/Pacific versus other ethnicity (1.5mmol/mol [0.1%], 95% CI -0.8, 3.7), and per-protocol analysis (-1.2mmol/mol [0.1%], 95% CI -4.1, 1.7). An interaction effect (-4.7mmol/mol [0.5%], 95% CI -8.1, -1.4) was found by OHTG status. Both treatments generated similar treatment satisfaction scores, although there was greater weight gain and greater improvement in lipids and liver enzymes after pioglitazone than vildagliptin. Conclusions: Comparative glucose-lowering by pioglitazone and vildagliptin is not different between Māori/Pacific people compared with other New Zealand ethnic groups. The presence of OHTG predicts greater glucose lowering by pioglitazone than vildagliptin.